PERUBAHAN DISFUNGSI ENDOTEL AORTA PADA TIKUS GALUR PUTIH REMAJA YANG TERPAPAR ALCOHOL TERHADAP PEMBERIAN CURCUMIN. - widiyanto, puguh; ekanto, budi (LPPM STIKES MUHAMMADIYAH GOMBONG, 2010)
The human body has the ability to prevent and correct endothelial dysfunction by producing antioxidants. This primary antioxidant will help prevent oxidation caused by free radicals, so the blood vessels endothelial dysfunction and will not experience does not occur in atherosclerotic arteries. Under these circumstances, where the number of free radicals in the blood is very excessive, an antioxidant that is produced by the body no longer effective, so that the necessary antioxidants from the outside (secondary). This research experiments, using post test only control group design. Statistical analysis is used for the T test, to assess the effect of antioxidants (curcumin). From the results of this study proves that there is a positive influence, that curcumin can prevent endothelial cell dysfunction with no incidence of characteristics of foam cells in the aorta of male teenagers who typhoid chronic alcohol exposure. Suggestion is to increase the consumption antiokidan (curcumin) to improve vascular endothelial damage (sclerosis). Â Keywords : Exposure to alcohol, the aortic endothelial dysfunction, provision of curcumin